ICTforAg 2024: A global convergence of agricultural innovation and digital transformation - Farmonaut (Farmonaut, 2024)
We are thrilled to share our experience at the recently concluded ICTforAg 2024, a landmark event that brought together the brightest minds in agricultural technology and digital innovation. This year’s conference, held from May 28-30, spanned five vibrant locations across the globe: Washington DC, New Delhi, Los Banos, Nairobi, and Texcoco. As pioneers in the agricultural technology sector, we at Farmonaut were honored to be part of this transformative gathering.